A novel approach to mapping land conversion using Google Earth with an application to East Africa. (October 2015) - Jacobson, Andrew; Dhanota, Jasjeet; Godfrey, Jessie; Jacobson, Hannah; Rossman, Zoe; Stanish, Andrew; Walker, Hannah; Riggio, Jason
Abstract: Effective conservation planning relies on the accurate identification of anthropogenic land cover. However, accessing localized information can be difficult or impossible in developing countries. Additionally, global medium-resolution land use land cover datasets may be insufficient for conservation planning purposes at the scale of a country or smaller. We thus introduce a new tool, GE Grids, to bridge this gap. This tool creates an interactive user-specified binary grid laid over Google Earth's high-resolution imagery. Using GE Grids, we manually identified anthropogenic land conversion across East Africa and compared this against available land cover datasets. Nearly 30% of East Africa is converted to anthropogenic land cover. The two highest-resolution comparative datasets have the greatest agreement with our own at the regional extent, despite having as low as 44% agreement at the country level. We achieved 83% consistency among users. GE Grids is intended to complement existing remote sensing datasets at local scales. Highlights: We introduce a new tool, GE Grids. This is the first free, customizable creator of raster data from Google Earth. GE Grids produces interactive, binary grids laid over Google Earth data. We use this tool to identify anthropogenic land cover in East Africa. Comparison of anthropogenic land cover to existing datasets finds key differences.